ZNF768 loss amplifies p53 action and reduces lung tumorigenesis in mice - Poirier, Audrey; Utecht, Timon; Villot, Romain; Gélinas, Yves; Mouchiroud, Mathilde; Kordahi, Manal; Kolnohuz, Alona; Pasteur, Coline; Roy, Joanny; Beaulieu, Marie-Josée; Orain, Michèle; Samson, Nolwenn; et al. (Oncogene, 2025)
Cell proliferation is a fundamental process required for organismal development, growth, and maintenance. Failure to control this process leads to several diseases, including cancer. Zinc finger protein 768 (ZNF768) is an emerging transcription factor that plays key roles in driving proliferation. In addition to controlling a gene network supporting cell division, ZNF768 physically interacts and inhibits the activity of the tumor suppressor p53. Although the importance of ZNF768 in promoting cell proliferation has been well demonstrated in vitro, the physiological and pathological roles of ZNF768 in vivo are still unknown. Here, we report the generation and characterization of a ZNF768 null mouse model. ZNF768 null mice are viable but show a growth defect early in life. Mouse embryonic fibroblasts (MEFs) isolated from ZNF768 null embryos exhibit higher p53 levels, premature senescence, and higher sensitivity to genotoxic stress. In line with these findings, ZNF768 null mice showed increased radiosensitivity. This effect was associated not only with higher expression of a subset of p53 target genes, but also with alterations in genes regulating transmembrane receptor signaling, cell adhesion, and growth. Because ZNF768 levels are elevated in tumors, we tested the impact of ZNF768 loss on cancer development in mice. Here, we show that ZNF768 deletion was sufficient to repress lung tumor development in a KRAS G12D -induced cancer mouse model. Overall, our findings establish ZNF768 as an important protein controlling cell proliferation that could potentially be targeted to reduce tumorigenesis.